ASSINATURA TRANSCRICIONAL DA IMUNOSSENESCÊNCIA EM LESÕES DE PACIENTES COM LEISHMANIOSE CUTÂNEA CAUSADA POR LEISHMANIA BRAZILIENSIS - Castro, Carlos Henrique Dettmann Fantecelle de (2020)
Imunosenescence is a word used to describe multiple characteristics observed at the immune cells compartment. Recently, our group demonstrated that circulating senescent T and NK cells accumulate in patients with localized cutaneous leishmaniasis (LCL), a